"MICE tourism – is your future" - Kadamboyev Behzod Shukhrat O’g’li (Genius Journals, 2022)
There is an increase in the number of tourists visiting Uzbekistan from distant foreign countries. In particular, in 2018, 325,000 tourists from distant foreign countries visited, and 35% of them, that is, 115,000, are Muslim tourists. In 2020, a total of 83,000 tourists from foreign countries visited our country, of which the number of Muslim tourists was 49,787 (59%). One type of tourism is MICE tourism. This tourism is very developed. MICE travel includes a number of components. Agents in this freield must provide complete travel and conference services for large and small groups and short and longterm events. Players in the MICE space include hotels, conference centers or cruise ships, food and beverage managers, logistics firms, private tour operators and transfer companies, incentive houses, professional trade organizations, and tourism offices
Keywords: Tourist; Foreign; Muslim Tourism; MICE Travel